2022
DOI: 10.3389/fneur.2021.788632
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's Disease With Visual Hallucinations Is Associated With Epileptiform Activity on EEG

Abstract: Background: Visual hallucinations (VHs) in Parkinson's disease (PD) are the cardinal symptoms which declare the onset of PD psychosis (PDP). The anthropomorphic and zoomorphic VHs of PD resemble those of Charles Bonnet syndrome and temporal lobe epilepsy. In both of these disorders electroencephalography (EEG) abnormalities have been described. We therefore sought to examine whether VHs in PD were associated with similar EEG abnormalities.Methods: This retrospective observational study searched the medical rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The underlying pathophysiology of VH in PD is still unclear 85 . Recent research has improved our understanding of the development of VH, emphasizing an association with cognitive decline and epileptiform discharges in the context of a more diffuse neurodegenerative process 85,86 . Nevertheless, dopaminergic medication is still the most important provoking factor for VH 84 .…”
Section: Resultsmentioning
confidence: 99%
“…The underlying pathophysiology of VH in PD is still unclear 85 . Recent research has improved our understanding of the development of VH, emphasizing an association with cognitive decline and epileptiform discharges in the context of a more diffuse neurodegenerative process 85,86 . Nevertheless, dopaminergic medication is still the most important provoking factor for VH 84 .…”
Section: Resultsmentioning
confidence: 99%
“…One explanation for the increased spike frequency could be depositions of α‐synuclein, which has been shown to induce network excitability in transgenic mouse models 31 that can escalate into seizure activity 32 . In addition, one study found an association between the densities of Lewy bodies in the temporal lobes and visual hallucinations, 12 and visual hallucinations have been linked to IED in the temporal lobes in patients with Parkinson's disease 13 . However, because of a high frequency of amyloid deposition in DLB, 33,34 it is also possible that AD related pathology leads to IED in DLB patients (ie, that amyloid is the common denominator leading to IED) or that the neurodegenerative process per se leads to IED.…”
Section: Discussionmentioning
confidence: 99%
“…32 In addition, one study found an association between the densities of Lewy bodies in the temporal lobes and visual hallucinations, 12 and visual hallucinations have been linked to IED in the temporal lobes in patients with Parkinson's disease. 13 However, because of a high frequency of amyloid deposition in DLB, 33,34 it is also possible that AD related pathology leads to IED in DLB patients (ie, that amyloid is the common denominator leading to IED) or that the neurodegenerative process per se leads to IED. However, studies in transgenic mouse models have found that α-synuclein aggregation alone is sufficient to cause network hyperexcitability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations